Perspectives on the impact of the OFSTED system of school inspection on primary schools: a case study approach - Blunsdon, P.A. (2002)
The activities of OFSTED and its impact are `a matter of high public interest' (Brunel University, 1999 p. 3) constituting as they arguably do, the central plank in governmental efforts to improve contemporary primary education. However, after almost a decade since its introduction, and in spite of a growing body of research into various aspects of the inspection process, there is relatively little which actually points to sustained improvements in either standards or classroom practice which can be directly attributed to OFSTED.